Intellectual Hospital Management System - Srinivasan, S; Bharathi, S. Prasanna; Chamundeeswari, G. (International Journal of Psychosocial Rehabilitation, 2020)
An intellectual healthcare management system has been built to support the patient at a hospital’s front desk. The patient will be able to learn about his / her health situation through physicians, appointment times, relevant services, laboratory tests and the necessary medication. The network provides the patients at the hospital entrance with an informed reception information facility. This also provides technical assistance to physicians to treat effectively and efficiently use the decision-making process of the system.